Renormalization constant for the local times of self-intersections of a diffusion process in the plane - Izyumtseva, O.L. (Український математичний журнал, 2008)
The self-intersection local times of a diffusion process in the plane are studied. The main result consists
in investigating asymptotic behavior of renormalizing constant for this local time. Розглянуто локальний час самоперетинів для дифузійного процесу на площині. Головним результатом є дослідження асимптотичної поведінки константи перенормування цього локального часу.